The Effect of Education Using Cartoon Media about Children’s Food on Increasing Mother’s Knowledge and Nutritional Status of Children with Bronchopneumonia - Ersiani Rante Bandaso; Umi Kalsum; Hesti Prawita Widiastuti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Bronchopneumonia is a disease that affects many children, it is even the main killer of toddlers in the world. This study aims to determine the effect of education using cartoon media about children's food on increasing mother's knowledge and nutritional status of children with bronchopneumonia aged 1-5 years in the orchid room at RSUD dr. Abdul Rivai Berau. This type of research uses a quasi-experimental design with pre-test and post-test. A sample of 32 people using Consecutive sampling. The results showed that there was an effect of education using cartoon media on mothers' knowledge about children's food with a p value of 0.000, and there was no effect of education using cartoon media on the nutritional status of children in the Orchid Room of Dr. Abdul Rivai Hospital Berau with a p value of 0.157. So it can be interpreted that there is an effect of education using cartoon media on mother's knowledge about children's food in the Orchid Room of Dr. Abdul Rivai Hospital Berau and there is no effect of education using cartoon media on the nutritional status of children in the Orchid Room of Dr. Abdul Rivai Hospital Berau.